The Mayo Endoscopic Score Is a Novel Predictive Indicator for Malignant Transformation in Ulcerative Colitis: A Long-Term Follow-Up Multicenter Study - Xu, Weimin; Liu, Fangyuan; Tang, Wenbo; Gu, Yubei; Zhong, Jie; Cui, Long; Du, Peng (Frontiers in Surgery, 2022)
Background: Data on the relative risk of malignant transformation in ulcerative colitis (UC) are insufficient. We investigated the potential value of the Mayo endoscopic score (MES) for predicting malignant transformation in UC patients. Methods: Data of UC patients evaluated at our institute from June 1986 to December 2019 were retrospectively analyzed. The MES used in the study was indicated the result of the first colonoscopy after hospitalization. We defined MES of 0–1 as low and MES of 2–3 as high. Univariable and multivariate logistic regression models were used for statistical analysis. Results: Among the 280 eligible UC patients with a median follow-up time of 14.0 (interquartile range, 10.0–18.0) years, those with a high MES were more likely to develop malignant transformation. High MES was positively correlated with the degree of malignancy and was an independent risk factor for UC-associated dysplasia and colorectal cancer (CRC, odds ratio [OR], 9.223; 95% confidence interval [CI], 1.160–73.323; p=0.036). Disease duration >5 years (OR, 2.05; 95% CI, 1.177–3.572; p = 0.011), immunomodulator use (OR, 4.314; 95% CI, 1.725–10.785; p = 0.002), biologics nonuse (OR, 3.901; 95%CI, 2.213–6.876; p < 0.001), and Hb<90 g/L (OR, 2.691; 95% CI, 1.251–5.785; p = 0.011) were contributing factors for high MES. Conclusion: High MES could be a novel predictor of malignant transformation in UC. Clinicians should optimize the use of biologics and immunomodulators early and actively correct anemia to improve the MES, then reduce the incidence of UC-associated dysplasia and CRC.